Bee glue (propolis) improves reproductive organs, sperm quality and histological changes and antioxidant parameters of testis tissues in rats exposed to excess copper - Seven, Ismail; Tatli Seven, Pinar; Gul Baykalir, Burcu; Parlak Ak, Tuba; Ozer Kaya, Seyma; Yaman, Mine (Wiley, 2020)
This study was designed to determine the effects of propolis on the sperm quality, antioxidant and histological parameters in the testicular tissues of male Sprague Dawley rats exposed to excessive copper (Cu). In this aim, 24 rats were randomly divided into four groups as follows: the control, Cu, Propolis and Cu+Propolis. When compared to control group, Cu administration significantly decreased sperm motility and concentration, increased total abnormal sperm rate. It caused a significant induction the malondialdehyde (MDA), and reduction the superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH) in testicular tissues. Also, it caused loss, disorganisation and vacuolation of the germinal epithelium, oedema of the interstitial tissues, proliferation of the interstitial cells, spilled immature spermatogenic cells in the lumen of some seminiferous tubules. A large number of active caspase-3-positive stained apoptotic cells and a significant decrease in Johnsen's testicular score were determined. However, significant ameliorations were observed in all sperm characteristics, MDA, SOD, CAT, GSH, seminiferous tubules, number of apoptotic cells and Johnsen's testicular score in Cu+Propolis group. Our results showed that oral supplementation of propolis had curative effect on the sperm quality, antioxidant and histological parameters in the testicular tissues of male Sprague Dawley rats exposed to Cu.
Keywords: antioxidant status; copper toxicity; histological changes; propolis; reproductive organs